Hubungan Kualitas Tidur dan Stres dengan Pola Makan Remaja di Kota Kediri saat Pandemi COVID-19 - Alya Pradnyaparamita; Lailatul Muniroh; Dominikus Raditya Atmaka (Media Gizi Kesmas, 2023)
Background: The transition from face-to-face classes to online classes is part of the education sector's strategy to comply with health protocols during the COVID-19 pandemic. However, this affects the sleep quality and stress levels in students. As many as 70% of high school students in East Java have poor sleep quality and only 30% have good sleep quality. Stress in adolescents is aggravated by limited access to tourism places, shopping centers, places of worship, sports grounds, and also meeting peers which are places to release stress. Poor sleep quality and stress levels increase the risk of eating pattern. Research data shows that during the pandemic of COVID-19, adolescents's eating patterns were disrupted, such as frequent snacking and eating high-calorie foods. A good diet during a pandemic is not only to shape nutritional status in the future but more importantly to maintain and increase body immunity to avoid transmission of the COVID-19 virus. Objective: This study aims to describe the quality of sleep, stress levels, and eating patterns of adolescents in Kota Kediri during pandemic of COVID-19 and to analyze the relationship between sleep quality and stress levels with eating patterns of adolescents in Kota Kediri during pandemic of COVID-19. Methods: This research was a cross-sectional observational study. The variables of this study were sleep quality, stress levels, and eating patterns. The instruments used were a respondent's characteristics questionnaire (gender, age, school, and address), sleep quality questionnaire, PSS-10 questionnaire to assess stress levels, and SQ-FFQ form with frequency of meals a day to assess eating patterns. The research locations were selected based on simple random sampling, that are SMAN 1, 3, and 4 Kediri City. The total sample is 101 students and divided based on proportional random sampling. Results: The results showed that 55 students (54.5%) had poor sleep quality, 46 students (45.5%) were classified having a mild level of stress, and 71 students (70.4%) had an adequate diet during pandemic of COVID-19. The results of the relationship test showed that there is a relationship between sleep quality and adequate eating patterns (p value = 0.007), and there is also a relationship between stress levels and the respondent's eating pattern (p value = 0.020). Conclusions: Poor sleep quality and mild stress levels have a relationship with adequate eating patterns in adolescents in the city of Kediri during pandemic of COVID-19.